Distal radius fractures in the athlete - Sobel, A. D.; Calfee, R. P. (Clinics in Sports Medicine, 2020)
Although the technical details of distal radius fracture fixation in athletes are largely similar to the general population, the issues surrounding the injury, desire to return to sport, and rehabilitation require specialized attention. Athletes are generally healthy, with a drive to recover and must balance the risk of long-term consequences of returning to play too early with the potential loss of scholarship, salary, or opportunities for advancement. Outcomes after nonoperative and operative treatment of distal radius fractures are generally excellent in athletes and return to the same level of sport occurs in most patients.